Association of Ang/Tie2 pathway mediators with endothelial barrier integrity and disease severity in COVID-19 - Moraes, Carla Roberta Peachazepi; Borba-Junior, Ivanio Teixeira; De Lima, Franciele; Silva, Jéssica Ribeiro Alves; Bombassaro, Bruna; Palma, André C.; Mansour, Eli; Velloso, Lício Augusto; Orsi, Fernanda Andrade; Costa, Fábio Trindade Maranhão; De Paula, Erich Vinicius (Frontiers in Physiology, 2023)
Endothelial barrier (EB) disruption contributes to acute lung injury in COVID-19, and levels of both VEGF-A and Ang-2, which are mediators of EB integrity, have been associated with COVID-19 severity. Here we explored the participation of additional mediators of barrier integrity in this process, as well as the potential of serum from COVID-19 patients to induce EB disruption in cell monolayers. In a cohort from a clinical trial consisting of thirty patients with COVID-19 that required hospital admission due to hypoxia we demonstrate that (i) levels of soluble Tie2 were increase, and of soluble VE-cadherin were decreased when compared to healthy individuals; (ii) sera from these patients induce barrier disruption in monolayers of endothelial cells; and (iii) that the magnitude of this effect is proportional to disease severity and to circulating levels of VEGF-A and Ang-2. Our study confirms and extends previous findings on the pathogenesis of acute lung injury in COVID-19, reinforcing the concept that EB is a relevant component of this disease. Our results pave the way for future studies that can refine our understanding of the pathogenesis of acute lung injury in viral respiratory disorders, and contribute to the identification of new biomarkers and therapeutic targets for these conditions.